If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6-3x=-5x+11x+33
We move all terms to the left:
6-3x-(-5x+11x+33)=0
We add all the numbers together, and all the variables
-3x-(6x+33)+6=0
We get rid of parentheses
-3x-6x-33+6=0
We add all the numbers together, and all the variables
-9x-27=0
We move all terms containing x to the left, all other terms to the right
-9x=27
x=27/-9
x=-3
| x2−4x=12 | | 4x2-17=-1 | | 7=74n(8) | | x*0.6=18 | | 7+⅔x=-1 | | 4p-16+6=10 | | 3(2+5m)-10=-22+6 | | 10+b/6=11 | | 9x+121=180 | | 2(0)-5=x | | -5x-1/3(9x+42)+70=0 | | 11+x=−5−x | | 3(2 | | 9+3x+7x-x=14 | | -5x+3=5x-7 | | 5q+6=2q+-2+q | | 1/2(4w+6)=1/3(9-3) | | 1/7(x+8)=10 | | 16–4x=20 | | (t+3)5/4=40 | | h=-16(2)^(2)+128(2)+320 | | 9x+2=117 | | 2(7x-2)+2x-4=48 | | 2(p-(4p+13)+3)=2(p+10) | | 2t-4+1=5 | | 7.4/m=10.6/11.8 | | −86=−2+7a | | 5x=25=25 | | 12x+10-7x=50 | | X+154+170=x+24 | | 6x=3×-2 | | 2/5m-1/5=7/10 |